IMMUNOLOGICAL MARKERS OF DIABETES MELLITUS IN VARIOUS CLINICAL VARIANTS OF THE DISORDER - G. G. Baiburina (Медицинская иммунология, 2014)
Abstract. We studied immune markers of diabetes mellitus, as well as their relations to clinical features at the onset of disease. The patients with newly diagnosed diabetes were examined. Antibodies to glutamate decarboxylase, islet-cell cytoplasm antigen, along with antibodies to insulin and basal C-peptide were tested. Immunological markers of type 1 diabetes mellitus have been identified in 58% of cases. The immune markers of type 2 diabetes mellitus have been discovered in 47.5% of cases. (Med. Immunol., 2011, vol. 13, N 6, pp 623-626)